Determination Of Child Care Rights Between Birthday Parents And Adopting Parents - Misran Misran; Aulil Amri; Nur Fatin Adila Binti Idereh (El-Hadhanah : Indonesian Journal Of Family Law And Islamic Law, 2023)
Adoption of children is regulated in the Deed of Registration of Appointment 1952 (Deed 253) for Muslims and non-Muslims and the Deed of Adoption 1952 (Deed 257) for non-Muslims. Among the cases involving the struggle for custody is the one that occurred at the Pahang Sharia High Court, in which the judge handed over a child to his biological parents while the child had been registered under the Deed of Registration of Appointment 1952 (Deed 253). Then, in the case at the Selangor High Court, the judge handed over custody rights to the adoptive parents while the adoption registration was invalid. There are two formulations of the problem in this thesis. Firstly, what are the considerations of the Pahang Sharia High Court judges in determining child custody between biological parents and adoptive parents? Second, what are the considerations of the judges of the Selangor High Court in determining child custody between biological parents and adoptive parents? This research uses the juridical-normative method and case studies. Data collection is also done with literature and documentation. The results of the study show that first, the consideration of the judges of the Pahang Sharia High Court in determining child custody of their biological parents is because the judge looks at their efforts to get their child back and they have full rights to the child. Second, the consideration of the judge of the Selangor High Court in determining child custody of the adoptive parents is important because the judge stated that the main thing is what is best for the child, and the child's biological parents also have several obstacles to looking after the child. Custody is closely related to the interests of the child and the guardians, if there is an imbalance in custody, then the rights and interests of the child need to take precedence over the interests of the guardians.